2018
DOI: 10.3390/children5110153
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Sleep and Cognitive Performance in Autism Spectrum Disorder (ASD): A Pilot Study

Abstract: Background: Sleep concerns are common in children with autism spectrum disorders (ASD). The impact of poor sleep on cognitive performance in ASD children is not well-established. We investigated the possible correlation between sleep quality in ASD children and cognitive performance. The Cambridge Neuropsychological Test Automated Battery (CANTAB) was administered to examine specific components of non-verbal cognition. Methods: The Children’s Sleep Habits Questionnaire (CSHQ) and actigraphy-measured data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Research suggests that sleep is associated with several cognitive domains in autism; however, this literature is scarce in the FASD population. Al-Backer and colleagues [ 27 ], for example, report that actigraphy-measured sleep duration is significantly associated with delayed response time in children aged between 7 and 10 years with a diagnosis of autism ( n = 18). Meanwhile, caregiver-reported insomnia and parasomnia symptoms can predict diminished working memory [ 28 ] and hyperactivity [ 29 ] in children.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that sleep is associated with several cognitive domains in autism; however, this literature is scarce in the FASD population. Al-Backer and colleagues [ 27 ], for example, report that actigraphy-measured sleep duration is significantly associated with delayed response time in children aged between 7 and 10 years with a diagnosis of autism ( n = 18). Meanwhile, caregiver-reported insomnia and parasomnia symptoms can predict diminished working memory [ 28 ] and hyperactivity [ 29 ] in children.…”
Section: Introductionmentioning
confidence: 99%
“…The association between sleep disturbances and cognitive functioning is not well established because some studies reported an increase of sleep difficulties in children with ASD and cognitive deficit ( 2 ) while others the occurrence regardless of the cognitive functioning ( 58 ). Moreover, the direction of this relationship needs to be clarified ( 59 ): do sleep problems cause cognitive deficits or vice versa ? Recent researches hypothesized that sleep is essential for optimizing cognitive development, memory and learning ( 31 , 58 ) and that chronic sleep deprivation has negative effects on cognitive and academic performance ( 31 , 41 ) probably influencing cerebral connectivity and creating aberrant neural pathways ( 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between these two disorders is known especially with regard to ASD and the link seems to be bidirectional. Indeed, if on the one hand the sleep disorder worsens cognitive skills and stereotypies, on the other hand it has been shown that treatments aimed at reducing stereotypical behaviors also improve sleep quality [ 45 , 46 ]. It is likely that also in subjects with PKS a similar mechanism is present.…”
Section: Discussionmentioning
confidence: 99%